Analisa Peluang, Ancaman, dan Tantangan Perdagangan Internasional Bagi Indonesia dengan Negara Cina - Amanda Irdan Natasya (CV. ITTC INDONESIA, 2026)
International trade plays a crucial role in promoting economic growth, enhancing national competitiveness, and strengthening a country's integration into the global economy. The trade relationship between Indonesia and China has become increasingly strategic due to the continuous growth of bilateral trade, investment, and economic cooperation. However, this relationship also presents various opportunities, threats, and challenges that require appropriate policy responses. Therefore, this study aims to analyze the opportunities, threats, and challenges of international trade between Indonesia and China, as well as to identify strategies for improving Indonesia's competitiveness amid the dynamics of global trade. This study employed a qualitative research method using a library research approach. Data were collected through documentation techniques from various secondary sources, including accredited scientific journals, books, scholarly articles, and official reports published by national and international institutions. Data were analyzed using content analysis, involving the stages of data reduction, data presentation, interpretation, and conclusion drawing. The findings indicate that Indonesia–China trade relations provide significant opportunities through increased exports of strategic commodities, foreign direct investment, industrial downstream development, technology transfer, and stronger integration into global value chains. Nevertheless, the study also identifies several threats, including intensified competition from imported products, dependence on raw materials and capital goods from China, and vulnerability to geopolitical changes and global supply chain disruptions. Furthermore, the main challenges faced by Indonesia include limited industrial competitiveness, insufficient technological innovation, high logistics costs, and the continued dominance of primary commodity exports. This study contributes to the development of international trade studies by strengthening the understanding of Indonesia–China bilateral trade from the perspectives of comparative advantage, competitiveness, and global value chains. The findings suggest that strengthening industrial downstream policies, improving human resource quality, fostering technological innovation, and diversifying export markets are essential strategies for enhancing Indonesia's competitiveness in international trade. Future research is recommended to employ empirical or mixed-method approaches by utilizing primary data and quantitative analysis to provide a more comprehensive understanding of the evolving dynamics of Indonesia–China trade relations.